PENGARUH REWARD, DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI PT BATAMITRA SEJAHTERA - wijaya, Vanessa; Wangdra, Yvonne (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
Finding out how PT. Batamitra Prosperous's workload, work discipline, and incentives all interact is the main goal of this study. Using a saturation sampling strategy, the study population consists of 125 workers. Descriptive analysis, assessment of data quality, regression, and hypothesis testing using SPSS as an aid are some of the data analysis approaches that are used. This study's data analysis shows that incentives significantly boost employee performance (t-value 2.034 > t-table 0.1757). The computed t-value of 5.547 > t-table 0.1757 also shows that work discipline has a positive and statistically significant effect on individual performance. Furthermore, the computed t-value of 4.673 > t-table 0.1757 indicates that workload substantially affects employee performance. Finally, the independent variables—reward, work discipline, and workload—simultaneously influence employee performance, as indicated by a calculated F-value of 38.571 > F-table 3.29. The coefficient of determination analysis yields a value of 0.489 or 48.9%, signifying that the contribution of work discipline, training, and communication variables to employee performance is 51.1%, while the remaining percentage is influenced by other variables beyond the scope of this research.